Differential anti-chemokine activity of Amblyomma variegatum adult ticks during blood-feeding. - Vancová, I; Slovák, M; Hajnická, V; Labuda, M; Simo, L; Peterková, K; Hails, R; Nuttall, P (2007)
Ticks secrete a cocktail of immunomodulatory molecules in their saliva during blood-feeding, including chemokine-binding factors that help control the activity of host immunocompetent cells. Here we demonstrate differential dynamics of anti IL-8 (CXCL8), MCP-1 (CCL2), MIP-1 (CCL3), RANTES (CCL5) and eotaxin (CCL11) activities in salivary gland extracts of adult Amblyomma variegatum. Unfed male and female ticks showed activity against all the chemokines except CCL5; anti-CCL11 activity was particularly high. However, during feeding the dynamics of anti-chemokine activity differed significantly between males and females, and varied between chemokines. In males, anti-chemokine activities increased, whereas in females they declined or increased slightly as feeding progressed. The exception was anti-CCL11 activity, which declined and then increased in both males and females. Comparison of salivary gland equivalents of individual ticks prepared at various feeding intervals revealed some differences that were most pronounced between individual females fed for 8 days. These observations reflect the feeding behaviour of male and female A. variegatum. They support the concept of 'mate guarding', in which males help their mates to engorge by controlling their host's immune response, and the possibility that ticks benefit from feeding together by exploiting molecular individuality.